1987
DOI: 10.7164/antibiotics.40.750
|View full text |Cite
|
Sign up to set email alerts
|

Arginomycin. Production, isolation, characterization and structure.

Abstract: Arginomycinis a new nucleoside antibiotic produced by Streptomyces arginensis. Arginomycin, C18H28N8O5, which inhibits the growth of Gram-positive bacteria and fungi in vitro, is structurally related to blasticidin S and found to be relatively non-toxic.Cultures of Streptomyces arginensis UC8632, grown in a complex medium were found to contain an antibacterial agent which was characterized by its paper chromatographic and TLCbehavior and its antibacterial spectrum. This antibiotic which exhibited activity agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…The reaction was carried out in the presence of L-arginine, ␣-ketoglutaric acid, L-aspartate, SAM, PLP, ArgM, and ArgN at 25°C for 3 h. Reactions were derivatized with DNS-Cl and quenched by 10% ethylamine, and reactions mixtures were subjected to an Agilent semipreparative column (Zorbax ODS, 5-m particle size, 9.4 by 250 mm). The same fragments of DNS-␤mArg were combined, concentrated, and analyzed for their 1 H NMR (500-MHz, methanol-d4) and 13 S11 to S12 in the supplemental material). Further COSY NMR clearly showed that the H · H protons of the ␣-carbon and ␤-methyl groups were correlated, thus proving the configuration of the (3R)-methyl group of DNS-␤mArg (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction was carried out in the presence of L-arginine, ␣-ketoglutaric acid, L-aspartate, SAM, PLP, ArgM, and ArgN at 25°C for 3 h. Reactions were derivatized with DNS-Cl and quenched by 10% ethylamine, and reactions mixtures were subjected to an Agilent semipreparative column (Zorbax ODS, 5-m particle size, 9.4 by 250 mm). The same fragments of DNS-␤mArg were combined, concentrated, and analyzed for their 1 H NMR (500-MHz, methanol-d4) and 13 S11 to S12 in the supplemental material). Further COSY NMR clearly showed that the H · H protons of the ␣-carbon and ␤-methyl groups were correlated, thus proving the configuration of the (3R)-methyl group of DNS-␤mArg (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the overall skeleton of arginomycin is highly similar to that of blasticidin S (BS) (Fig. 1), a representative peptidyl nucleoside antibiotic exhibiting strong inhibitory activity against rice blast caused by Pyricularia oryzae Cavara (2), arginomycin showed much lower toxicity to mice (1). They differ from each other only in the modification of the L-arginine-derived guanidino side chain (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although BS is most potent as an antifungal agent, it also exhibits antibacterial (32), antiviral (16,17), and antitumor activities (39). Several other peptidyl nucleoside antibiotics have close structural similarities to BS (1,7,15,19,20,36,37); they all consist of a cytosine hexuronic nucleoside unit and a basic amino acid side chain.…”
mentioning
confidence: 99%
“…As shown in Figure 2, SDS-PAGE of the purified CGA synthase from the last step (lanes 8 CGA synthase, isolated from S. griseochromogenes, catalyzes the formation of CGA from UDP-glucuronic acid and cytosine in the biosynthesis of the peptide-nucleoside antibiotic BS (14) and is also quite likely involved in the biosynthesis of a number of other known nucleoside antibiotics (1,7,15,19,20,36,37). Functionally, CGA synthase belongs to the family of UDPGTs; although UDP-GTs are common in mammalian metabolism and at least two have been reported for fungi (10,40), they have not been previously reported for a prokaryotic organism.…”
mentioning
confidence: 99%